Peningkatan Kemampuan Fonologi Anak Usia Dini Melalui Kegiatan Bermain Berbasis Bahasa di TK YLPI Riau: Fonologis - Yuliawan, Tri; Shomary, Sudirman; Mukhlis, Muhammad; Roziah, Roziah; Hermaliza, Hermaliza; Kamarudin, Kamarudin; Wahyuni, Astri (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
Phonological ability is a fundamental aspect of early childhood language development, closely linked to later literacy and communication skills. This study, titled "Phonological Ability of Early Childhood through Language-Based Play Activities at YLPI Riau Kindergarten," investigates the effectiveness of language-based play in enhancing phonological skills among young learners. The research is grounded in the understanding that play serves as a natural medium for language acquisition in early childhood education settings. A qualitative descriptive approach was employed to explore how structured language-based play activities contribute to children's phonological development. The subjects of this study were children aged 4–5 years at YLPI Riau Kindergarten. Data collection techniques included observation, interviews with teachers, and documentation of children's play activities. Observations focused on children’s ability to recognize and manipulate sounds, including rhyming, syllable segmentation, and initial sound identification. Data were analyzed using qualitative content analysis to identify patterns and themes related to phonological development during play. The analysis emphasized how specific types of language-based play—such as storytelling, rhyming games, sound matching, and singing—supported the development of phonological awareness in a playful and engaging context. The results revealed that language-based play activities significantly contributed to the improvement of children’s phonological abilities. Children showed increased awareness of sounds, improved pronunciation, and greater ability to distinguish phonemes. Teachers also played a key role by facilitating and scaffolding the play in ways that promoted language learning. In conclusion, language-based play activities are effective pedagogical tools for fostering phonological development in early childhood. The findings highlight the importance of integrating purposeful play in early education curricula to support foundational language skills in a developmentally appropriate manner